2021
DOI: 10.3389/fvets.2021.675570
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Grow-Out Affects Campylobacter jejuni Colonization Fitness in Coincidence With Altered Microbiota and Lipid Composition in the Cecum of Laying Hens

Abstract: Campylobacter jejuni is one of the leading causes of gastrointestinal illness worldwide and is mainly transmitted from chicken through the food chain. Previous studies have provided increasing evidence that this pathogen can colonize and replicate in broiler chicken during its breeding; however, its temporal kinetics in laying hen are poorly understood. Considering the possible interaction between C. jejuni and gut microbiota, the current study was conducted to address the temporal dynamics of C. jejuni in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Uncl. Fusicatenibacter belongs to the family Lachnospiraceae and was previously associated with host GIT health (Biddle et al, 2013), and detected in the ileum and caeca of laying hens (van der Eijk et al, 2019) with a constant presence from day 1 to week 40 (Asakura et al, 2021). A recent study, using metagenomic analysis, showed several protologues for new candidatus Fusicatenibacter (Gilroy et al, 2021), this bacterial group was more abundant in crop and might be involved in the first steps of feed digestion together with M. funiformis.…”
Section: Figurementioning
confidence: 99%
“…Uncl. Fusicatenibacter belongs to the family Lachnospiraceae and was previously associated with host GIT health (Biddle et al, 2013), and detected in the ileum and caeca of laying hens (van der Eijk et al, 2019) with a constant presence from day 1 to week 40 (Asakura et al, 2021). A recent study, using metagenomic analysis, showed several protologues for new candidatus Fusicatenibacter (Gilroy et al, 2021), this bacterial group was more abundant in crop and might be involved in the first steps of feed digestion together with M. funiformis.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, the temporal dynamics of Campylobacter spp. colonization in laying hens is not yet well-understood [ 32 ]. When comparing our result (43%) with other reports, it was higher than those reported in Greece (13.3%) [ 33 ] and Australia (11%) [ 17 ], but lower than those observed in Finland (86%) [ 34 ], Italy (65%) [ 35 ], and Sri Lanka (64%) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This occurred at the same time when most laying hens became negative and remained negative for C. jejuni [50]. The role of bacterial members of the family Ruminococcaceae within the intestinal microbiota of chickens was reviewed by Rychlik [42].…”
Section: Discussionmentioning
confidence: 99%
“…Only 16 weeks after oral infection with C. jejuni , the Ruminococcaceae family exhibited an increased relative abundance that plateaued and thus was stably present within the caecal microbiota [50]. This occurred at the same time when most laying hens became negative and remained negative for C.…”
Section: Discussionmentioning
confidence: 99%